METHODS SUGGESTED FOR PROTECTING CHILDREN FROM THE NEGATIVE EFFECTS OF ENTERTAINING DIGITAL DEVICES - Recep DEMİR (Fırat University, 2020)
The cartoons are extremely amusing animations that substitute for the tales of the past which were filled with secrets. Today, real-like animations can be produced after 200 years of historical development. However, throughout this development process, animations produced for the child have been criticized in many categories including violence, obscenity, sexuality, negative precedent etc. despite the national and international laws on child protection. In parallel with the development of technology, new digital products have been developed as alternatives to television programs and these products have given rise to a much bigger world of show business with the help of the internet connection. The gamer enters to the playground and starts to become a part of the game due to the development of technology such as virtual reality, 4D and 5D. The rise in the quality and attraction of entertainment increased the addiction to the digital screen and distracted children from real life. In addition, with the rapid development of urbanization, children whose play areas have shrunk had to be at home, and they had to meet their inherent game needs through digital entertainment. Therefore, many social, physical, mental problems were encountered. The harmful aspects of the technology have come to the fore rather than the benefit of it. In this study, video games and cartoons, which are the two main elements of the digital entertainment world, are discussed and the risks that these products cause for children are also discussed with examples from the literature. Then, efforts were made to bring solution suggestions to eliminate these risks.